EXFOLIATION OF NANOGRAPHENE FROM WASTE BATTERIES AND ITS APPLICATION IN METHYLENE BLUE DYE REMOVAL - K, Bogeshwaran; Kumar, K. Sathish; Karunanithi, B.; Srividhya, M.; Gowri, G. (Journal of the Chilean Chemical Society, 2021)
In the process of recovering wealth from waste, graphene has been exfoliated electrochemically from the graphite rods used in waste batteries (AA and AAA). This exfoliated graphene is analyzed using Raman spectroscopy, TEM, and found to be a mesoporous nanoparticle with a BET surface area of 710.396 m2/g and a pore size of 14.81 Å. Highly toxic methylene blue(MB) dye is being chosen for adsorption using the as-prepared graphene by varying the graphene dosage, contact time, temperature, and MB dye concentration. From UV, XRD, and FTIR the adsorption of MB on graphene has been confirmed. The graphene’s adsorption at 300C was 272 mg/g. The adsorption followed Temkin isotherm and the mechanism was pseudo-second-order. Thermodynamic relations show the adsorption process to be spontaneous and chemical in nature.